2013
DOI: 10.9738/cc112.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Effecting Mortality in Acute Mesenteric Ischemia and Mortality Rates: A Single Center Experience

Abstract: The objective of this study is to discuss the effective factors on morbidity and mortality in patients who were operated on for acute mesenteric ischemia. Between 2006 and 2011, 95 patients, who underwent emergent surgery for acute mesenteric ischemia, were analyzed retrospectively. The study group consisted of 56 men (58.9%) and 39 women (41.1%), with an average age of 68.4 ± 14.4 years. Elapsed time between the onset of the symptoms and the surgical operation was less than 24 hours in 47 (49.5%) cases, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 26 publications
(29 reference statements)
7
53
3
2
Order By: Relevance
“…This has been suggested previously by Aliosmanoglu et al who observed a significant difference in mortality rates between those suffering intestinal necrosis and those that had combined intestinal and colonic involvement 14 . Other authors have demonstrated similar findings with small and large bowel involvement identified as risk factors for perioperative mortality 2 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This has been suggested previously by Aliosmanoglu et al who observed a significant difference in mortality rates between those suffering intestinal necrosis and those that had combined intestinal and colonic involvement 14 . Other authors have demonstrated similar findings with small and large bowel involvement identified as risk factors for perioperative mortality 2 .…”
Section: Discussionsupporting
confidence: 61%
“…Depending on the classification of ischemia and treatment procedure, mortality ranges from 17.7% to 47% with rates increasing in those that underwent bowel resection 16 . Mortality has been shown to be higher in those that have colonic ischemia in the setting of intestinal necrosis 14 . While this may reflect a synchronous disease process, our analysis did not demonstrate an increased risk of mortality with isolated colonic resection.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a specific method for the diagnosis of AMI generally results in delayed diagnosis. Mortality rates have been reported in different studies between 30% and 100%, and in this study the rate was found to be 60% (16)(17)(18)(19)). …”
Section: Discussionmentioning
confidence: 62%
“…3,9 This disease usually affects patients in higher age group who have multiple comorbid conditions4 and both advanced age and presence of comorbid conditions, especially more than one simultaneously are the significant risk factors adversely affecting mortality in our study which is consistent with most of the other studies. 4,6,7,10 Both these factors are synergistic but independent determinants of mortality. Gender and presence or absence of addictions have no influence as per our study on mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In spite of all attempts towards early diagnosis and treatment mortality in patients with acute mesenteric vascular ischemia leading to intestinal gangrene remains high. 4,7,8 This high mortality rate prompted us to undertake this study to identify prognostic indicators of mortality in these patients to provide guidance for deciding management strategies.…”
Section: Introductionmentioning
confidence: 99%